Allocation of fishing possibilities, incentives and outcomes: Insights from Basque fishermen's organisations in Spain. (November 2015) - Aranda, Martin; Murillas, Arantza
Abstract: There is a need for effective mechanisms to be in place in order to allocate fishing possibilities. This seems crucial so that distributional concerns regarding this issue are properly addressed. This paper aims at providing insights into the allocation of fishing possibilities from Basque fisheries. We put forward this case in terms of its outcomes to the incentives deployed by the allocation system. The institutional substratum plays a key role in the outcomes of the system. In fact, the fishermen's traditional collective approach predominates even though the management system tends towards individual rights allocation and promotion of rights transferability. This is particularly notable in the case of inshore Basque fisheries. Highlights: The Spanish allocation system tends to individualized allocation of rights. The institutional substratum plays a key role in the outcomes of the allocation system. POs contribute to create a co-management by partnership. Collective management of rights predominates in the Basque inshore sector although rights are allocated individually.